PENGARUH MANAJEMEN RISIKO KREDIT TERHADAP KINERJA PERBANKAN DI BURSA EFEK INDONESIA - Herry Hutabarat; Sarton Sinambela (Universitas Bunda Mulia, 2018)
This study aim is to test the effect of credit risk management (independent variable) on Return on Asset (ROA) and on Return on Equity (ROE) (dependent variables). Credit risk management is projected with capital adequacy ratio (CAR), non performing loan (NPL), operational cost to operating income, loss reserves, and interest margin (IM). The results showed that from five independent variables and two dependent variables, only 3 independent variables had significant effect on ROA or ROE, which are; Non-performing loan, operational cost to operating income and interest rate. Capital adequacy variable only has significant effect on ROE. The reserve loss variable only has a significant effect on ROA.